Lama Rawat Kurang dari Empat Jam di Instalasi Gawat Darurat sebagai Indikator Mutu Pelayanan dan Penerapannya di Indonesia: Tinjauan Pustaka - Sulistio, Septo; Gani, Ascobat (PT Kalbe Farma Tbk., 2025)
The emergency department (ED) operates 24 hours in a day, 7 days, in a a week, to provide emergency medical care, but with the growing number of visits, delays in patient assessment and treatment can impact care quality. A common performance indicator used to measure ED efficiency is the length of stay (LOS) of less than four hours, reflecting both service quality and patient flow management. This target has been widely implemented in a few countries, such as the United Kingdom and Australia to enhance ED operations. In Indonesia, a similar target has been set for national referral hospitals, aiming for 90% compliance. However, initial evaluations show that only a small fraction of hospitals meet this target, raising concerns about its feasibility. Despite these challenges, the four-hour LOS remains a relevant quality indicator in EDs. Achieving this goal requires collaborative efforts from allhealthcare stakeholders to improve ED efficiency and patient care. This literature review explores the feasibility and challenges of this target in all parts of Indonesia.